Josef Pieper on Medieval Truth and Martin Heidegger’s Wahrheitsbegriff - Rehman, Rashad (Conatus - Journal of Philosophy, 2022)
Josef Pieper’s critique of Martin Heidegger’s Wahrheitsbegriff (concept of truth) has been virtually ignored in both Pieper and Heidegger scholarship; however, Pieper’s critique of Heidegger is both lethal and affirmative. On the one hand, Pieper makes a strong case against Heidegger’s Wahrheitsbegriff in “Vom Wesen der Wahrheit” and yet on the other he affirms his thesis that “the essence of truth is freedom.” This paper attempts to mend this gap in the literature by first presenting Heidegger’s “Vom Wesen der Wahrheit,” the essay in which Heidegger explicates his concept of truth. Second, I exegete the critique of Josef Pieper found in his “Heideggers Wahrheitsbegriff.” Third, I conclude the paper by contextualizing Pieper’s critique within Pieper’s Werke, and make a note of the philosophical insights derivative from Pieper’s less than simple relationship to Heidegger.